2023
DOI: 10.1007/s00415-023-11581-w
|View full text |Cite
|
Sign up to set email alerts
|

The phenotypic spectrum of pathogenic ATP1A1 variants expands: the novel p.P600R substitution causes demyelinating Charcot–Marie–Tooth disease

Abstract: Background Charcot–Marie–Tooth disease (CMT) is a genetically and clinically heterogeneous group of inherited neuropathies. Monoallelic pathogenic variants in ATP1A1 were associated with axonal and intermediate CMT. ATP1A1 encodes for the catalytic α1 subunit of the Na+/ K+ ATPase. Besides neuropathy, other associated phenotypes are spastic paraplegia, intellectual disability, and renal hypomagnesemia. We hereby report the first demyelinating CMT case due to a novel ATP1A1 variant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…A loss of the function of normal NKA activity has been reported to cause age-related hearing loss in a mouse model (13). A recent study reported a patient with the p.Pro600Arg variant in ATP1A1 who exhibited similar clinical manifestations to ours, including demyelinat-ing CMT and severe sensorineural deafness (8). Unfortunately, the diagnosis of ANSD in that case was not confirmed by further audiological evaluations, including ABR (8); however, ANSD may be a common cause of sensorineural deafness in this variant.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…A loss of the function of normal NKA activity has been reported to cause age-related hearing loss in a mouse model (13). A recent study reported a patient with the p.Pro600Arg variant in ATP1A1 who exhibited similar clinical manifestations to ours, including demyelinat-ing CMT and severe sensorineural deafness (8). Unfortunately, the diagnosis of ANSD in that case was not confirmed by further audiological evaluations, including ABR (8); however, ANSD may be a common cause of sensorineural deafness in this variant.…”
Section: Discussionsupporting
confidence: 71%
“…The c.1799C>G (p. Pro600Arg) variant was previously reported in a 50-year-old patient with CMT2DD and more severe sensorineural deafness (8). This variant has not been described in healthy individual databases, including the Exome Aggregation Consortium (https://gnomad.broadinstitu te.org).…”
Section: Case Reportmentioning
confidence: 98%
“…NKAs formed by the α1 subunit are ubiquitous, while α2 pumps predominate in skeletal muscle and glia, and α3 pumps are expressed in neurons. Notably, sensory and motor neurons express both α1 and α3 isoforms, with α1 predominating in axons ( 4 ), which may explain why α1 disease-associated variants predominantly cause CMT type 2 in which axonal degeneration leads to progressive strength and sensory loss starting from the distal limbs, although an ATP1A1 variant causing demyelinating CMT was recently described ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological studies in Xenopus oocytes and adrenal NCI-H295R cells expressing disease-related NKA α1 variants reported depolarizing inward currents through most (but not all) variants linked to hyperaldosteronism ( 2, 8, 10, 11 ) or hypomagnesemia with refractory seizures ( 7, 12 ), providing a plausible gain-of-function mechanism for these disease-associated variants. However, variants causing neuropathies seem to lack such inward “leak” currents ( 4-7, 9-11 ). Moreover, functionally characterized CMT variants impair NKA function to distinct degrees.…”
Section: Introductionmentioning
confidence: 99%